Good Governance and Terrorism in Nigeria - Hakeem Olatunji Tijani (Universitas Medan Area, 2022)
Nigeria has been fighting a war against terrorism for long time. It is uncertain if the war can be won because it has been exacerbated by lack of good governance. People have been deprived of economic opportunities, they are socially insecure and politically docile. This has had dire consequences for their human emancipation, which good governance attempts to build. Terrorism has found convenient marketability among the people as failure of the state in good governance has meant easy recruitment for terrorist activities. Therefore, for the war to be effectively prosecuted and won, sources of impediments to good governance need to be identified and addressed squarely. In other words, the curtailment of terrorism in Nigeria is hinged on abilities of the Nigerian state to promote good governance. Presently, Nigeria has been bedeviled with the twinning tragicness of terrorism and lack of good governance, the two signify failure for the state. Dishearteningly, today, Nigeria is on the verge of becoming a failed state because of its failure in good governance, Nigeria has continually witnessed decline in indicators of good governance. It has become incapable to provide security to citizens as acts of terrorism, banditry and kidnapping have been aggravated in the country.